Changes in Intrarenal Resistive Index Following Electromagnetic Extracorporeal Shock Wave Lithotripsy - Mohseni, Mohammad Ghasem; Khazaeli, Mahziar; Aghamir, Seyed Mohammad Kazem; Biniaz, Farzad (Urology Journal, 2009)
Introduction: Our aim was to study the changes in resistive index (RI) of the ipsilateral and contralateral kidneys following electromagnetic extracorporeal shock wave lithotripsy (SWL) of the kidney calculi. Materials and Methods: Using color Doppler ultrasonography, the RI was determined in 21 patients with unilateral caliceal and pelvic kidney calculi. The RI of the interlobar renal arteries were measured for the regions near and far from the calculi (distance, less and more than 2 cm), before, 30 minutes after, and 1 week after SWL. The same measurements were carried out for the contralateral kidney. Changes in the RI values and their relation with age were evaluated. Results: The RI near the calculi increased 30 minutes after SWL from 0.594 Â± 0.062 to 0.620 Â± 0.048 (P = .003; 95% confidence interval, 0.020 to 0.073), but returned to the pre-SWL values 1 week later. The RI values of the region remote from the calculus and in the contralateral kidney did not change significantly. There was a weak correlation between age and the RI far from the calculus before and 1 week after SWL. There were no relationships between the RI and age, sex, weight, blood pressure, and smoking. Conclusion: The results suggest that SWL of the kidney calculi changes the RI only near the calculus which is immediate, transient, and not age-related.